Web Broadcasting and Multi User System - Sangeetha, A; Tamilarasi, M (International Journal of Computer Sciences and Engineering, 2025)
This system has been successfully developed and hosted in the different server configurations and undergoes different kind of tests in the environment of multi user systems any number of user can enjoy the videos with multi access. It has enough functionality beyond web TV to any home entertainment system. It has a quick access to the thousands of video files available in various categories. It provides a high quality performance for the videos to be watched out by the viewers. When multiple video sources are live-encoded and transmitted over a common wireless network, each stream needs to adapt its encoding parameters to wireless channel fluctuations, so as to avoid congesting the network. We present a stochastic system model for analyzing multi-user congestion control for live video coding and streaming over a wireless network. Variations in video content complexities and wireless channel conditions are modeled as independent Markov processes, which jointly determine the bottleneck queue size of each stream. Interaction among multiple users is captured by a simple model of random traffic contention. Using the model, we investigate two distributed congestion control policies: the approach based on stochastic dynamic programming (SDP) and a greedy heuristic. Compared to fixed-quality coding with no congestion control, performance gains in the range of 0.5-1.3 dB in average video quality are reported for both schemes from simulation results under various video and channel characteristics